Про деякі теоретичні напрями удосконалення діяльності персоналу органів та установ виконання покарань - Воробей, П.; Vorobei, P.; Колб, С.; Kolb, S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статті здійснено аналіз основних змістовних елементів, що визначають сутнісну спрямованість та соціально-правову природу діяльності персоналу органів та установ виконання покарань України, а також сформульовані науково обґрунтовані шляхи щодо удосконалення правового механізму з цих питань.The article analyzes the main content elements that determine the essence and socio-legal nature of the bodies and institutions for the execution of sentences and their staff activities in Ukraine. The study reveals scientifically grounded ways to improve the legal mechanism on these issues. The author supports and develops the idea of creating a special unit within the system of the Ministry of Justice of Ukraine, which is independent from the state criminalexecutive system of Ukraine. This unit will conductinternal inspections at the penal institutions andconsider the complaints of the convicts. It will turn the penitentiary service into a civilized institution based on the principles of respect for human rights and fundamental freedoms, the rule of law and standards of the UN and the Council of Europe. Constructive reforms must be implemented in such a way as not to destroy the foundations of the existing structure, but rather to improve it, bring it to a more civilized level. Consequently, the future law must reflect the necessary, substantial, sustainable, repetitive provision for the execution of criminal penalties/sentences and probation, determine the limits of its sustainability, the principles of organization and functioning.
Theoretical Approaches to the Improvement of the Activity of the Bodies and Institutions for the Execution of Sentences and Their Personnel
Keywords: органи та установи виконання покарань; сфера виконання покарань; виконання покарань; персонал; суб’єкт правовідносин; об’єкт правової охорони; правоохоронні органи; bodies and institutions for the execution of sentences; scope of punishment; execution of punishment; personnel; subject of legal relationships; object of legal protection; law enforcement agencies